Sparse matrix technology - Pissanetzky, Sergio (Academic Press, Inc., 1984)
The fundamental methods and procedures of sparse matrix technology are introduced and described in detail, with discussion reaching the point where the reader can understand the specialized literature on each subject. Wherever possible, a unified treatment is provided. The purpose of the book is to bring sparse matrix technology within reach of engineers, programmers, analysts, teachers, and students. It should be helpful to anyone wishing to develop sparse matrix software, or improve the understanding of software currently employed. Teachers will find an elementary presentation of sparse matrix methods, ideas, and examples of application at a professional level.